A Near‐Infrared‐Responsive Quaternary Ammonium/Gold Nanorod Hybrid Coating with Enhanced Antibacterial Properties. Issue 11 (13th October 2022) - Zhao, Yu-Qing; Xiu, Zongpeng; Wu, Ruonan; Zhang, Lujiao; Ding, Xiaokang; Zhao, Nana; Duan, Shun; Xu, Fu-Jian
Abstract : Biomedical device‐associated infection (BAI) is a common symptom in hospitals. To solve this problem, the biomedical device needs fast, efficient, and safe antibacterial methods to prevent infection. Herein, a strategy for surface antibacterial functionalization is proposed, using mild photothermal effect and quaternary ammonium salt to common sterilize. Au nanorods (NRs) and quaternized N, N′ ‐dimethylethylenediamine (QDED) (quaternary ammonium salt) are modified on the surface of polyurethane (PU) to fabricate PU‐Au‐QDED. First of all, stable and recyclable mild photothermal radiation is achieved by low‐power near‐infrared (NIR) light irradiation, and then in a shorter time of NIR irradiation, mild photothermal effect promotes the disturbance of the alkyl chain of quaternary ammonium salt to destroy the bacterial membrane, together with quaternary ammonium salt QDED that has fast and efficient antibacterial property, especially against multidrug‐resistant bacteria. Meanwhile, mild photothermal effects, together with quaternary ammonium salt QDED, have good biocompatibility. Among all of the samples, PU‐Au‐Q5 demonstrates fast, efficient, and safe antibacterial performances. At the same time, the antibacterial mechanisms are further studied. Finally, the in vivo antibacterial properties are verified by the subcutaneous implantation animal model. The present work provides a facile and promising approach to develop high‐performance antibacterial biomedical devices. Abstract : A hybrid nanocoating with rapid bactericidal property and high biocompatibility is developed based on Au nanorods and quaternary ammonium salts.